DEGRADATION MODEL OFPOLYETHYLENE TEREPHTHALATE BY ESCHERCHIA COLI BACTERIA - Talib, Taufan (BAREKENG: Jurnal Ilmu Matematika dan Terapan, 2018)
Degradation of Polyethylene Terephthalate (PET) using Escherchia Coli (E-Coli) bacteria in awhole cell biocatalys system. E-Coli bacteria will produce LC-Cutinase enzyme surface of the cell and coupled with PET, so PET can decompose. LC-Cutinase reaction and PET lasts for three days. Models that are formed already can explains the phenomenon of PET degradation